1998
DOI: 10.1159/000009995
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Gestational Thrombocytopenia and the Syndrome of Hemolysis, Elevated Liver Enzymes, and Low Platelet Count (HELLP Syndrome)

Abstract: Objective: To define the clinical features of gestational thrombocytopenia and to determine its relationship to the syndrome of hemolysis, elevated liver enzymes, and low platelet count (HELLP syndrome). Study Design: Retrospective cohort study. We reviewed the records of 24 women with gestational thrombocytopenia among 637 nonpreeclamptic women who had serial determinations of the platelet count during pregnancy between 1992 and 1995. Gestational thrombocytopenia was defined as an antenatal gradual decline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 23 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…While George et al . stated that, for women with mild thrombocytopenia who do not need treatment, the distinction from ITP may not be important during the pregnancy, Minakami et al . reported that GT is a high‐risk factor for HELLP syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While George et al . stated that, for women with mild thrombocytopenia who do not need treatment, the distinction from ITP may not be important during the pregnancy, Minakami et al . reported that GT is a high‐risk factor for HELLP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Because of these findings, we consider our study to be of clinical significance. While George et al 19 stated that, for women with mild thrombocytopenia who do not need treatment, the distinction from ITP may not be important during the pregnancy, Minakami et al 20,21 reported that GT is a high-risk factor for HELLP syndrome. Although the final diagnosis can be made only after delivery, careful monitoring is necessary for women with thrombocytopenia with platelet counts of less than 100 000/μL, even for cases that do not require treatment during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…3.2% of pregnant women develop liver dysfunction peri‐partum . Liver dysfunction is likely to occur in pregnant women with gestational thrombocytopenia leading to diagnosis of the syndrome of hemolysis, elevated liver enzymes, and low platelets (HELLP syndrome). However, liver dysfunction can occur even in the absence of thrombocytopenia; some patients with acute fatty liver of pregnancy (AFLP) lack thrombocytopenia, but have liver dysfunction at presentation .…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, this issue has not been extensively studied. Because women who exhibit a gradual decline in AT‐III activity and/or platelet count appear to be at higher risk of developing of the HELLP syndrome (15, 16) and because the number of multifetal pregnancies is increasing due to ovulation induction and in vitro fertilization (17), it is important to better characterize the changes in these parameters in twin and singleton pregnancies. Accordingly, we prospectively determined AT‐III activity and platelet count in 56 women with twin pregnancies and 692 women with singleton pregnancies to determine whether antithrombin III activity and platelet count are more likely to decrease in women with twin pregnancies than singleton pregnancies.…”
mentioning
confidence: 99%